Buku Cerita Aktivitas STEM Islami sebagai Media Penguatan Literasi dan Profil Pelajar Pancasila - Metafisika, Kartika; Zahroh, Lailatus; Utomo, Khoirul Budi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Storybooks are an effective medium for strengthening literacy and can act as a learning resource to cultivate character. In storybooks, games and activities can also be developed to grow the skills of students. Learning that links Science, Technology, Engineering, and Mathematics (STEM) in an integrated manner began to develop in various countries and began to be applied in Indonesia through a prototype curriculum. STEM learning is known to be effective in developing students' collaboration skills, thinking skills, and motor skills through project implementation. This article will discuss 1) the role of Islamic STEM Storybooks to strengthen student literacy, and 2) how to bring up the elements of the Pancasila Student Profile which consists of Belief in One God and Noble Morals, Global Diversity, Critical Thinking, Creative Thinking, Independence, and Mutual Cooperation in Islamic STEM Activity Storybooks.